Author Correction: Biologically driven DOC release from peatlands during recovery from acidification. Issue 1 (December 2018) - Kang, Hojeong; Kwon, Min; Kim, Sunghyun; Lee, Seunghoon; Jones, Timothy; Johncock, Anna; Haraguchi, Akira; Freeman, Chris
The original version of this Article contained an error in the Acknowledgements, which incorrectly omitted from the end the following: 'In particular, we thank the staff of the Centre for Ecology and Hydrology (including A. Burden, N. Ostle and C. Evans) in relation to a NERC grant involving CF & TJ (NE/E011748/1; 2007–2010), which established the sites from which the UK samples were subsequently collected.' This has been corrected in both the PDF and HTML versions of the Article.